Circles and spirals - Prabhu, R.; Larson, A.M.; Colfer, C.J.P. (Routledge, 2021)
This chapter begins with a look at the Greek concepts of ouroboros and triskelion, emphasizing the static versus dynamic nature of social phenomena, linking ACM to the latter. The authors systematically re-examine the chapters in this book, seeking clarity on what ACM is. They then examine how successful it has been in its various manifestations, highlighting both strengths and weaknesses. The next section looks in depth at two major African programmes to take the insights from ACM, usually conducted at a local level, to a broader scale or higher level, encompassing larger geographical areas (SHARED and Greening Africa). This section is valuable in its demonstration of some of the differences that emerge, but also the applicability, when one attempts ACM at grander scales. The chapter concludes with some thoughts on changing global paradigms and the philosophical implications of ACM for people’s lives.